Abnormal regional spontaneous neural activity in treatment‐refractory depression revealed by resting‐state fMRI - Wu, Qi‐Zhu (Hum Brain Mapp, 2010)
Treatment‐refractory depression (TRD) represents a large proportion of the depressive population, yet has seldom been investigated using advanced imaging techniques. To characterize brain dysfunction in TRD, we performed resting‐state functional MRI (rs‐fMRI) on 22 TRD patients, along with 26 matched healthy subjects and 22 patients who were depressed but not treatment‐refractory (NDD) as comparison groups. Results were analyzed using a data‐driven approach known as Regional Homogeneity (ReHo) analysis which measures the synchronization of spontaneous fMRI signal oscillations within spatially neighboring voxels. Relative to healthy controls, both depressed groups showed high ReHo primarily within temporo‐limbic structures, and more widespread low ReHo in frontal, parietal, posterior fusiform cortices, and caudate. TRD patients showed more cerebral regions with altered ReHo than did NDD. Moderate but significant correlations between the altered regional ReHo and measures of clinical severity were observed in some identified clusters. These findings shed light on the pathophysiological mechanisms underlying TRD and demonstrate the feasibility of using ReHo as a research and clinical tool to monitor persistent cerebral dysfunction in depression, although further work is necessary to compare different measures of brain function to elucidate the neural substrates of these ReHo abnormalities. Hum Brain Mapp, 2011. © 2010 Wiley‐Liss, Inc.